The impact of the Nutri-Score front-of-pack nutrition label on purchasing intentions of unprocessed and processed foods: post-hoc analyses from three randomized controlled trials - Manon Egnell; Pilar Galan; Morgane Fialon; Mathilde Touvier; Sandrine Péneau; Emmanuelle Kesse-Guyot; Serge Hercberg; Chantal Julia (BMC, 2021)
Abstract Background The Nutri-Score summary graded front-of-pack nutrition label has been identified as an efficient tool to increase the nutritional quality of pre-packed food purchases. However, no study has been conducted to investigate the effect of the Nutri-Score on the shopping cart composition, considering the type of foods. The present paper aims to investigate the effect of the Nutri-Score on the type of food purchases, in terms of the relative contribution of unpacked and pre-packed foods, or the processing degree of foods. Methods Between September 2016 and April 2017, three consecutive randomized controlled trials were conducted in three specific populations - students (N = 1866), low-income individuals (N = 336) and subjects suffering from cardiometabolic diseases (N = 1180) - to investigate the effect of the Nutri-Score on purchasing intentions compared to the Reference Intakes and no label. Using these combined data, the proportion of unpacked products in the shopping carts, as well as the distribution of products across food categories taking into account the degree of processing (NOVA classification) were assessed by trials arm. Results The shopping carts of participants simulating purchases with the Nutri-Score affixed on pre-packed foods contained higher proportion of unpacked products - especially raw fruits and meats, i.e. with no FoPL -, compared to participants purchasing with no label (difference of 5.93 percentage points [3.88-7.99], p-value< 0.0001) or with the Reference Intakes (difference of 5.27[3.25-7.29], p-value< 0.0001). This higher proportion was partly explained by fewer purchases of pre-packed processed and ultra-processed products overall in the Nutri-Score group. Conclusions These findings provide new insights on the positive effect of the Nutri-Score, which appears to decrease purchases in processed products resulting in higher proportions of unprocessed and unpacked foods, in line with public health recommendations.